Studies in the New World tribe Anisoscelini Laporte, 1832 (Heteroptera: Coreidae: Coreinae): updated distributions, nomenclatural changes, and keys to the genera of the tribe and the species of Anisoscelis Latreille, 1829 and Bitta Osuna, 1984 - Jr., John M. Leavengood; Brailovksy, Harry; Barrera, Ernesto (Zootaxa, 2024)
Ninety new country records are recorded for 44 species of Anisoscelini Laporte, 1832 (Heteroptera: Coreidae: Coreinae). Informal distributional records are recognized and included, and updated distributions are provided for all accounted species. The following new synonymy is proposed: Malvana Stål, 1865 (= Belonomus Uhler, 1869, n. syn.) and Malvana serrulata Stål, 1865 (= Belonomus annulaticornis Uhler, 1869, n. syn.). The rank of one genus is reinstated: Bitta Osuna, 1984, stat. resurr. (formerly a subgenus of Anisoscelis Latreille, 1829). The following new or restored combinations are proposed: Bitta affinis (Westwood, 1840), comb. reins., Bitta alipes (Guérin-Méneville, 1833), comb. reins., Bitta gradadia (Distant, 1881), comb. reins., Bitta hymeniphera (Westwood, 1840), comb. reins., Bitta lurida (Brailovsky, 2016), comb. nov., and Bitta podalica Brailovsky & Mayorga, 1995, comb. reins.. We also present dichotomous keys to the twenty-nine genera of Anisoscelini, and to the species of the genera Anisoscelis Latreille, 1829 and Bitta Osuna, 1984.